Ultrafast photodissociation dynamics and nonadiabatic coupling between excited electronic states of methanol probed by time-resolved photoelectron spectroscopy - Champenois, Elio G.; Greenman, Loren; Shivaram, Niranjan; Cryan, James P.; Larsen, Kirk A.; Rescigno, Thomas N.; McCurdy, C. William; Belkacem, Ali; Slaughter, Daniel S. (My University, 2019)
The electronic and nuclear dynamics in methanol, following 156 nm photoexcitation, are investigated by combining a detailed analysis of time-resolved photoelectron spectroscopy experiments with electronic structure calculations. The photoexcitation pump pulse is followed by a delayed 260 nm photoionization probe pulse to produce photoelectrons that are analyzed by velocity map imaging. The yields of mass-resolved ions, measured with similar experimental conditions, are found to exhibit the same time-dependence as specific photoelectron spectral features. Energy-resolved signal onset and decay times are extracted from the measured photoelectron spectra to achieve high temporal resolution, beyond the 20 fs pump and probe pulse durations. When combined with ab initio calculations of selected cuts through the excited state potential energy surfaces, this information allows the dynamics of the transient excited molecule, which exhibits multiple nuclear and electronic degrees of freedom, to be tracked on its intrinsic few-femtosecond time scale. Within 15 fs of photoexcitation, we observe nuclear motion on the initially bound photoexcited 21A″ (S2) electronic state, through a conical intersection with the 11A′ (S3) state, which reveals paths to photodissociation following C–O stretch and C–O–H angle opening.